Prosthetic Management of a patient with Occular Defect with Occular Prosthesis - A case report. - Singh, Laxman; S, Suresh; Bharathi, Swarajya; Jaiswal, Satyam (Journal of Orofacial Research, 2011)
The eye is a vital organ not only in terms of vision but also being an important component of facial expression. Throughout history, human eye has been mentioned as the most precious of gifts . The rehabilitation of a patient who has suffered from an ocular loss , requires a prosthesis that will provide the optimum cosmetic and functional results. A 45 year-old male reported to the Department of Prosthodontics, Darshan dental college,Udaipur,Rajasthan, with a missing left eye. Treatment was initiated with psychological counselling and reassured treatment outcome regularly during treatment. Treatment of such cases includes implants and acrylic eye prosthesis. Although ocular implant eye prosthesis has superior outcome, due to economic factors it may not be advisable in all patients. So a custom-made ocular prosthesis is a good alternative. A case of a custom-made ocular acrylic prosthesis is presented here, which had acceptable fit, retention and esthetics.